2018
DOI: 10.3389/fmicb.2018.02533
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal Fungi and Bacteria Associated With Cervical Intraepithelial Neoplasia and High-Risk Human Papillomavirus Infections in a Hispanic Population

Abstract: The human cervicovaginal microbiota resides at an interface between the host and the environment and may affect susceptibility to disease. Puerto Rican women have high human papillomavirus (HPV) infection and cervical cancer rates. We hypothesized that the population structure of the cervicovaginal bacterial and fungal biota changed with cervical squamous intraepithelial lesions and HPV infections. DNA was extracted from cervix, introitus, and anal sites of 62 patients attending high-risk San Juan clinics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 93 publications
12
100
0
Order By: Relevance
“…Our systematic search resulted in 11 eligible included articles (Figure ), of which the general characteristics and quality assessment are described in the Supplementary material (Tables S2 and S3). Reasons for exclusion of the articles excluded after full text screening are reported in the Supplementary material (Appendix S2), with 15 studies lacking essential data for inclusion in the network meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Our systematic search resulted in 11 eligible included articles (Figure ), of which the general characteristics and quality assessment are described in the Supplementary material (Tables S2 and S3). Reasons for exclusion of the articles excluded after full text screening are reported in the Supplementary material (Appendix S2), with 15 studies lacking essential data for inclusion in the network meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…In summary, through the use of longitudinal samples from the CVT cohort we investigated and identified key features of the cervicovaginal microbiome potentially associated with progression of HR-HPV infection [28, [53][54][55][56] (e.g., Gardnerella and subsequent increase vaginal microbial diversity). Additional studies are required to validate the model proposed in this report.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Discoveries resulting from human microbiome research have demonstrated that microbes play a role in the susceptibility to HPV and neoplasia [1][2][3]. Oncogenic high-risk human papilloma virus (HPV+H) infections are associated with the development of carcinomas, a malignancy on the rise in multiple populations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In Mexican women, Sneathia spp. were considered cervical biomarkers for neoplasia [14], while in Puerto Ricans, a loss in Lactobacillus was associated with an increase in Atopobium vaginae and Gardnerella vaginalis in patients with CIN3 lesions with HPV+H, low-risk HPV, or both co-infections [2]. Cervical microbiota of a majority of HIV negative black South African women was not dominated by Lactobacillus, suggesting that such cervical microbiota may be a contributing factor to the high burden of HIV and HPV infections among black women [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation